(untitled) - Seward, Jack (Tokyo, Japan, 1971)
The book is highly recommended for business people, travelers, and anyone else with an interest in Japan and things Japanese. It has specific vocabulary and sentences for airline personnel, immigration officials, hotel employees, bartenders, restaurant staff, doctors, students, home-stay hosts, etc.
Keywords: National characteristics, Japanese